On a combinatorial structure of the problems of optimal packing of geometric objects - Yakovlev, S.V. (Reports of the National Academy of Sciences of Ukraine, 2017)
The problem of optimal layout of geometric objects with given shape and physico-metric parameters is considered. Combinatorial structure is allocated by forming the multiple tuples of physico-metric parameters. On the basis of a functional presentation of the permutations of tuples, an equivalent setting, in which physico-metric parameters are variables, is formulated. The proposed approach is illustrated by the problem of packing of unequal circles into a circle with minimal radius.